ANALISIS LITERASI LINGKUNGAN SISWA SMP - Santoso, Ririn; Roshayanti, Fenny; Siswanto, Joko (JPPS (Jurnal Penelitian Pendidikan Sains), 2021)
This study aims to determine the environmental literacy of students at SMP Negeri 5 Taman. The sample in this study were students of class VII totaling 45 students. The collection of student environmental literacy data in this study uses the standard assessment of Middle School Environmental Literacy Survey (MSELS). Data collection techniques used in this study include interview methods and test methods. Data analysis and data interpretation in this assessment are data reduction, categorization, synthesis, and working hypothesis. The results showed that the environmental literacy of SMP Negeri 5 Taman students had an average value of 58,48%, which was sufficient criteria. The results of the study are based on environmental literacy indicators, each indicator obtains a different average value of ecological knowledge of 8,71 % (sufficient criteria), cognitive skills of 3,24% (less criteria), environmental awareness attitude of 89,11 % (good criteria), and environmentally responsible behavior of 45,20% (good criteria).